Kajian Tekno-Ekonomi Penerapan Insinerator Waste-to-Energy di Indonesia (Kasus pada Kota “X") - Manis Yuliani; Geby Otivriyanti; Naufal Riadhi Yusuf; Ayudia Mutiara Fani; Wahyu Purwanta (Jurnal Teknologi Lingkungan, 2022)
In order to realize net zero emissions in waste sector, the government encourages the application of Waste-to-Energy (WtE) thermal process technology in 12 cities in Indonesia. There are many obstacles and challenges in implementing WtE as an alternative for waste management, starting from changes in consistency of regulations, environmental issues as well as technical and economic feasibility. Therefore, this study aims to examine the Techno-Economics of WtE Incinerator Implementation in Indonesia by taking the case in City "X" as an illustration for stakeholders in making decisions. The methods used include the desk study, direct observation, and interviews. In this study, City "X" becomes a model for the implementation of WtE with a waste processing capacity of 1,500 tpd which is a typical waste generation in big cities in Indonesia. City set a target to reduce 80–90% of waste volume. After technology selection stage, the MGI was selected as the main WtE unit. The plant is designed with a capacity of 1,500 tons/day of waste with a calorific value of 6,276 kJ/kg, 26% plant efficiency, 8,000 hours/year operation so that it will produce 28.33 MW of electricity or energy equivalent to 226,633 MWh/year. This electrical power will be used for internal purposes by 15% so that the total net electricity for the PLN grid is 24.08 MW. This WtE has a capital expenditure (Capex) of 2.2 billion IDR/ton/day and operational expenditure (Opex) 167 million IDR /year/ton per day with an estimated construction in 2025. The electricity price obtained from this capacity is 1,819 IDR/kWh. Based on the estimated value of the cost of capital, the selling price of electricity and the assumption that the loan will be returned for 10 years with interest rate of 6%, the WtE project gets a tipping fee of 642,779 IDR/ton of waste.